The search for habitable exoplanets - Siffert, Beatriz (Cadernos de Astronomia, 2022)
Since the discovery of the first planets outside the Solar System, the so-called exoplanets, in 1992, more than 5000 exoplanets have been found and there are thousands of other candidates currently under study. Once we discovered the existence of other planetary systems, it becomes natural to ask ourselves if they could also host life. In this context, the multidisciplinary science of astrobiology, which studies the origin and evolution of life in the Universe, gains increasingly visibility. In this paper we present a brief review on the search for exoplanets and the main results so far regarding their astrobiological interest. Starting with the definition of stellar habitable zone, which is the region around a star where it is, in principle, possible to hold liquid water on the surface of a rocky planet, we will then comment on the search for life in the Solar System and describe the main methods currently used to find new exoplanets. We will also present some examples of known exoplanets that are particularly interesting from an astrobiological point of view. We will end by commenting on the search for the so-called biosignatures and technosignatures, which are expected to indicate the existence of life outside Earth, and current and future missions with greatest potential for new discoveries in this field.
Keywords: astrobiology; exoplanet; habitable zone; primary transit; radial velocity